(untitled) (Journal of Teaching and Research in English Literature, 2025)
This paper analyses the depiction of space in Daisy Hasan’s The To-Let House (2010) in light of Foucault’s notion of heterotopias. Heterotopias are alternate spaces that serve as counter-sites that challenge established notions and discourses. They are real-world spaces that perform a unique function or possess a symbolic meaning within society. It is argued that the physical spaces within the domestic environment described in the novel The To-Let House act as heterotopias on multiple levels. How the crafting of space is used as a means to convey the psycho-social states of the characters are discussed. Literary cartography, pioneered by Robert Tally, is used in addition to the concept of heterotopia to understand how the spaces serving as counter sites reveal an understated layer of storytelling. This analysis attempts to understand how physical space functions as a reflection of the emotional struggles and yearnings of the characters and the intricacies between space and identity.